ETHNOPEDAGOGY-BASED TEACHING MATERIALS TO IMPROVE ELEMENTARY SCHOOL TEACHERS' LITERACY AND NUMERACY: A PRELIMINARY STUDY - Alimuddin, Nurkhaerat; Nurwahidah; Yeni Suranti, Ni Made; Ibrahim; Fauzi, Asri (BIOCHEPHY: Journal of Science Education, 2025)
This study aims to identify teachers' perceptions and needs for the development of ethnopedagogy-based teaching materials to improve literacy and numeracy. The study employed a quantitative descriptive approach, utilizing data collection techniques that involved distributing questionnaires to elementary school teachers from diverse cultural backgrounds. Data were analyzed using descriptive statistics to examine the tendency of respondents' answers regarding aspects of literacy and numeracy, as well as local cultural integration in the learning process. The results show that the majority of teachers are aware of the importance of literacy and numeracy and support the implementation of ethnopedagogy; however, they encounter obstacles in the availability of relevant teaching materials and limited professional development opportunities. These findings suggest a pressing need for the development of teaching materials that not only enhance literacy and numeracy skills but also foster students' cultural identities through contextual learning. This study is an initial contribution to the development of an ethnopedagogy-based teaching material model as a strategic solution in improving the quality of numeracy learning in elementary schools while supporting the preservation of local culture in education.